Induced neodymium luminescence in sol–gel derived layered double hydroxides - Smalenskaite, Aurelija (2019)
The Mg3Al1−xNdx layered double hydroxides (LDHs) were synthesized via aqueous sol–gel synthetic route and the influence of the Nd3+ doping on the Mg3Al1−xNdx LDHs properties was estimated for the dopant concentration varied in the range of 1–10 mol%. The microstructure and morphology of the synthesized LDHs were revealed by X-ray diffraction analysis and scanning electron microscopy. The neodymium doped LDHs were characterized by the luminescence emission spectra.